1997
DOI: 10.1016/s0167-4889(97)00012-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal epidermal growth factor precursor: proteolytic processing in an in vitro cell-free system1Presented as a communication at the 29th Annual Scientific Meeting of the European Society for Clinical Investigation, Cambridge, UK, April 2–5, 1995. Eur. J. Clin. Invest. 25 (suppl. 2), A53, Abstract no. 305, 1995.1

Abstract: The enzymatic processing of the membrane-bound renal epidermal growth factor precursor (proEGF) could be an important step in the control of nephrogenic repair consecutive to kidney insult. The enzyme machinery responsible for that processing was examined in a cell-free system consisting of renal membranes isolated from kidney homogenates by differential centrifugation, and incubated in vitro. After a 24-h incubation at 37 degrees C, 6-14% of membrane-bound proEGF was processed and soluble products with EGF im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The entire ectodomain of the precursor can be shed from the cell through a proteolytic cleavage that involved a zinc-dependent metalloprotease activity that appears not to be TACE but can be activated by both PKC-dependent and -independent pathways. However, these experimental results obtained with cultured cells, are in conflict with those obtained with membrane fractions of both kidney (45,46) and mammary gland (47). Indeed, these preparations contain a membrane bound proteolytic activity that colocalizes with pro-EGF.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The entire ectodomain of the precursor can be shed from the cell through a proteolytic cleavage that involved a zinc-dependent metalloprotease activity that appears not to be TACE but can be activated by both PKC-dependent and -independent pathways. However, these experimental results obtained with cultured cells, are in conflict with those obtained with membrane fractions of both kidney (45,46) and mammary gland (47). Indeed, these preparations contain a membrane bound proteolytic activity that colocalizes with pro-EGF.…”
Section: Discussionmentioning
confidence: 72%
“…It has already been shown that, in vitro, mature EGF could be released from its precursor through the action of different type of proteases; acidic protease such as pepsin (36) or serine-proteases such as trypsin (22,39,41) and plasmin (44). Moreover, membrane fractions of both kidney (45,46) and mammary gland (47) contain a membrane-bound proteolytic activity that colocalized with pro-EGF and released soluble EGF from its membraneassociated precursor. Based on its sensitivity to a set of inhibitors, it was shown to belong to the serine-protease family.…”
Section: Epidermal Growth Factor (Egf)mentioning
confidence: 99%
“…The ectodomain can function in an autocrine, paracrine or endocrine fashion to antagonize or stimulate cellular events. As an example the ligand EGF is released by ectodomain cleavage from the cell surface where it is expressed as a type 1 membrane protein, proEGF (24). Similarly the intracellular fragment can traffic to the nucleus or another intracellular organelle to serve a new function.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the biosynthetic pathway of pro-EGF maturation into different intermediate soluble and transmembrane forms has not been studied in detail (77)(78)(79). The cytoplasmic domain of pro-EGF has been described to have its intrinsic biological activity.…”
Section: Discussionmentioning
confidence: 99%